Legal Liabilities and Duties of a Doctor: Part 1 - Kirti Singh; Bhumika Sharma; Arshi Singh; Anju Lal (Delhi Journal of Ophthalmology)
The current ethos of degenerating doctor patient relationship is a cause of concern for medical fraternity. Ever increasing rate of medical malpractice cases, doctor patient conflict is draining the doctor of financial resources and professional satisfaction respectively, not to mention loss of dignity and peace. A key weapon in our defense against charge of ”professional misconduct” is appropriate knowledge of what all is entailed by conduct as per legal language. This article is part of two sections, the first one deals with medical negligence, dereliction of duty, consumer protection act in relation to physicians, informed consent and documentation of records.